Legal Certainty on Corruption in Banking offences in the Indonesian Criminal Justice System - Mohammad Choirul Anam; Dien Nufitasari; Retno Catur Kusuma Dewi; Bambang Sukarjono (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2025)
Introduction to the Problem: Corruption is one of the most damaging crimes to a country's economy. One of the corruption cases in Indonesian banking through a fictitious credit scheme as happened in Bank Jabar Banten (BJB) Tangerang Branch proves how important the application of law is to overcome corruption in banking. Purpose/Study Objectives: The challenges that the author will study can be formulated based on the background of the problems described above, namely: 1). How is the legal analysis of banking corruption based on court decisions in Indonesia? 2). How is the construction of legal certainty governing criminal offences of banking corruption in Indonesia?. Design/Methodology/Approach: Normative research was the methodology used. Banking crime is a broad category of crime that occurs within the banking industry, according to the research findings. Due to the complexity of these crimes, the Corruption Act is used in the prosecution of the perpetrators. Findings: The results of this study indicate that criminal offences occurring in the banking sector in the case of Bank Jabar Banten (BJB) Tangerang Branch can be applied to the Corruption offence as “Lex Specialis” even though the modus operandi falls into the territory of other laws and regulations, namely the Banking Law, but the defendant's “Mens Rea” and the elements that are more fulfilled are the articles of corruption so that the application of the Corruption offence to the defendant Bank Jabar Banten (BJB) Tangerang Branch is appropriate. Juridical construction in the crime of banking corruption based on the justice system in Indonesia can be built through the approach of the principle of “logische specialiteit”, the principle of “systematische specialiteit”, the principle of “Lex Consumen Derogat Legi Consumptae”. Paper Type: General Review